2005
DOI: 10.1084/jem.20040463
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic stimulation blocks endothelial cell activation and leukocyte recruitment during inflammation

Abstract: Endothelial cell activation plays a critical role in regulating leukocyte recruitment during inflammation and infection. Based on recent studies showing that acetylcholine and other cholinergic mediators suppress the production of proinflammatory cytokines via the α7 nicotinic acetylcholine receptor (α7 nAChR) expressed by macrophages and our observations that human microvascular endothelial cells express the α7 nAChR, we examined the effect of cholinergic stimulation on endothelial cell activation in vitro an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
352
0
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 448 publications
(384 citation statements)
references
References 43 publications
22
352
0
6
Order By: Relevance
“…In contrast to its suppressive effect on TNF release from endotoxin-stimulated WT peritoneal macrophages, choline did not suppress TNF release from α7nAChR KO cells. These results strengthen the concept that α7nAChR expressed on macrophages and other immune cells plays a critical role in controlling inflammatory responses (4,26).…”
Section: Discussionsupporting
confidence: 74%
“…In contrast to its suppressive effect on TNF release from endotoxin-stimulated WT peritoneal macrophages, choline did not suppress TNF release from α7nAChR KO cells. These results strengthen the concept that α7nAChR expressed on macrophages and other immune cells plays a critical role in controlling inflammatory responses (4,26).…”
Section: Discussionsupporting
confidence: 74%
“…Systemic inflammation with release of inflammatory cytokines has been shown to be associated with insulin resistance and an increased prevalence of gestational diabetes (70)(71)(72)(73). Nicotine has been shown to block the release of inflammatory cytokines, suppressing the phosphorylation of molecules responsible for the inhibition of insulin action through a series of transcriptional events mediated by the NFkB or JNC pathways (74.75), as well as endothelial activation and leukocyte recruitment (76). Thus, cigarette smoking, by inhibiting inflammatory activity linked to insulin resistance, could diminish hyperglycaemia.…”
Section: Discussionmentioning
confidence: 99%
“…However, this immune-sensory function of vagal afferents is not unique to the vagus nerve, and all sensory fibers distributed throughout the body, such as skin, muscle, and all mucosal surfaces, can respond to immunological stimuli and transmit this information to the central nervous system. However, studies by Tracey and colleagues (Borovikova et al, 2000;Saeed et al, 2005) have suggested that the efferent vagus nerve, and thus the parasympathetic nervous system, plays a unique and powerful role in regulating systemic and localized inflammatory processes, primarily by inhibiting macrophage production of TNF-α. They have shown that vagal efferent stimulation can inhibit endotoxin-induced sepsis and TNF-α production, as well as localized inflammation induced in a dermal airpouch.…”
Section: Role Of the Vagus Nerve And Parasympathetic Nervous Systemmentioning
confidence: 99%
“…Among the inflammatory cytokines produced by macrophages, the production and release of the inflammatory cytokine TNF-α is the primary cytokine that is regulated by the sympathetic nervous system. It is of further interest that exactly this same inflammatory cytokine has been the focus of the "cholinerigic anti-inflammatory hypothesis" (Borovikova et al, 2000;Saeed et al, 2005).…”
Section: Effects Of Stress On Splenic Macrophagesmentioning
confidence: 99%